First person - Christiaan Veerman (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Christiaan Veerman is first author on 'Genetic variation in GNB5 causes bradycardia by augmenting the cholinergic response via increased acetylcholine-activated potassium current (IK,Ach)', published in DMM. Christiaan is a resident in cardiology in the lab of Prof. Bezzina at University of Amsterdam, The Netherlands, investigating pathophysiological mechanisms of inheritable cardiac arrhythmia syndromes using human induced pluripotent stem cells.